Physical-preparation recommendations for elite rugby sevens performance - Schuster, J.; Howells, D.; Robineau, J.; Couderc, A.; Natera, A.; Lumley, N.; Gabbett, T. J.; Winkelman, N. (International Journal of Sports Physiology and Performance, 2018)
Rugby sevens, a sport new to the Olympics, features high-intensity intermittent running and contact efforts over short match durations, normally 6 times across 2 to 3 d in a tournament format. Elite rugby sevens seasons often include over a dozen competitive tournaments over less than 9 months, demanding deliberate and careful training-stress balance and workload management alongside development of the necessary physical qualities required for competition. Focus on running and repeated power skills, strength, and match-specific conditioning capacities is advised. Partial taper approaches in combination with high-speed running (>5m/s from GPS measures) before and between tournaments in succession may reduce injury rates and enhance performance. In a sport with substantial long-haul intercontinental travel and repetitive chronic load demands, management of logistics including nutrition and recovery is inclusive of the formula for success in the physical preparation of elite rugby sevens athletes.